2018
DOI: 10.3389/fneur.2018.00718
|View full text |Cite
|
Sign up to set email alerts
|

MRI Markers and Functional Performance in Patients With CIS and MS: A Cross-Sectional Study

Abstract: Introduction: Brain atrophy is a widely accepted marker of disease severity with association to clinical disability in multiple sclerosis (MS). It is unclear to which extent this association reflects common age effects on both atrophy and function.Objective: To explore how functional performance in gait, upper extremities and cognition is associated with brain atrophy in patients with Clinically Isolated Syndrome (CIS) and relapsing-remitting MS (RRMS), controlling for effects of age and sex.Methods: In 27 pat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 64 publications
1
9
0
Order By: Relevance
“…In our study, we only found correlations of T25FW with the volume of thalamus and mean upper cervical spinal cord area. Thalamic volume has also previously been correlated with 9‐HPT in RRMS patients 45,46 . In our SPMS cohort, we found a correlation of 9‐HPT with thalamic, corpus callosum, mean upper cervical spinal cord area, and total lesion volumes.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In our study, we only found correlations of T25FW with the volume of thalamus and mean upper cervical spinal cord area. Thalamic volume has also previously been correlated with 9‐HPT in RRMS patients 45,46 . In our SPMS cohort, we found a correlation of 9‐HPT with thalamic, corpus callosum, mean upper cervical spinal cord area, and total lesion volumes.…”
Section: Discussionsupporting
confidence: 76%
“…Thalamic volume has also previously been correlated with 9-HPT in RRMS patients. 45,46 In our SPMS cohort, we found a correlation of 9-HPT with thalamic, corpus callosum, mean upper cervical spinal cord area, and total lesion volumes. This indicates that hand function may be highly complex and dependent on multiple cerebral areas.…”
Section: Discussionmentioning
confidence: 73%
“…3,4 Thalamic atrophy was associated with fatigue, 5,6 cognitive impairments, 7,8 decrease of walking speed, 9 and higher disability. 10,11 Measuring thalamic volume may be a good surrogate biomarker for clinical trials and, probably, routine practice. 4,11,12 Thalamic atrophy in MS can be related to either primary damage in the thalamus or distant damage of afferent or efferent thalamic fibers.…”
mentioning
confidence: 99%
“…The major limitation of the present study is represented by the limited MRI assessment. We have not considered the thalamic atrophy that has proved to occur early in the disease course (Azevedo et al, 2018) Indeed, Rasche et al (2018) have recently showed that thalamic volume, but not other brain volumes (normalized brain volume, white matter volume, gray matter volume) correlates with a functional measure of motor dexterity (9-hole peg test). However, data are lacking on the possible correlation between MRI measure and specific gait parameters assessed by a very refined approach such as GA.…”
Section: Discussionmentioning
confidence: 99%